Intraspecific variation of mitochondrial cytochrome b gene sequences of the Japanese Marten Martes melampus and the Sable Martes zibellina (Mustelidae, Carnivora, Mammalia) in Japan - Naoko Kurose (2018)
To assess genetic variations of two Japanese species of the genus Martes, the Japanese marten M. melampus and the sable M. zibellina, the whole regions (1,140 base pairs) of the mitochondrial cytochrome b gene were sequenced. Intraspecific variable sites were different between these two species, and most substitutions were transitions resulting in synonymous mutations. Molecular phylogenetic trees exhibited genetic differentiation between the two species. Genetic variations among M. melampus from Honshu, Shikoku, and Kyushu were larger than those among M. zibellina from Hokkaido. Genetic distance between cytochrome b haplotypes did not correlate to geographic distance between sampling localities. This result suggests the introgression of mitochondrial DNA haplotypes between local populations, probably resulting from incomplete geographic isolation, and/or their recent expansion on each island during a short period.